Equity research: Juventus F.C. overview and valuation - Ananyan, Tigran (2022)
The purpose of this thesis is to provide a recommendation on whether to buy or sell Juventus's stock on December 3, 2021. The author chose to include Discounted Cash Flows, Multiples, and Multivariate methods. The author reached a target price of €0.35,€2.26, €0.25, €0.15and €0.3331respectively.As the results obtained from multiples valuation are not reasonable the price was determined by averaging 50%/50% the valuation findings from the Multivariate and DCF techniques with a target price of €0.3338.The firm is overvalued as the Market Quote = €0.4144, resulting in a sell recommendation.